Demand of auto parts factors affecting it and how this demand affects supply of auto parts in Iloilo City - Garachico, Grace C.; Genterola, Brenda G.; Gustilo, Stephanie M.; Regencia, Rizza Mae S.; Rivera, Shirley M.
This study aimed to identify factors affecting the demand of auto parts and how this demand affects supply of auto parts. The area of this study was Iloilo City. The data for the study were gathered through survey questionnaires. The respondents to the survey were the auto parts dealers. In analyzing the data, frequency count and percentage analysis was used. Out of seventy (70) auto parts dealers, forty (40) respondents were identified and were given questionnaires. The major findings of the study are : 1) according to the auto parts dealers, income of the customers affects the demand of auto parts; 2) accidents also affect the demand of auto parts; 3) maintenance of automobile influences the demand of the auto parts; 4) wear out problems affect the demand of auto parts; 5) in-demand brands are available to most of the auto parts dealers; and 6) regardless of the demand of specific auto parts, dealers supply almost all the auto parts to cater the needs of the customers.